Measurement of the topological branching fractions of the tau lepton. - Akerlof, C; Baranko, G; Baringer, P; Beltrami, I; Blockus, D; Bonvicini, G; Brabson, B; Bylsma, BG; Chapman, J; Cork, B; DeBonte, R; Derrick, M; et al. (1985)
We report new and precise measurements of the decay branching fractions of the lepton to one and three charged particles. The data, corresponding to an integrated luminosity of 176 pb-1, were collected by the high resolution spectrometer HRS at the e+e- storage ring PEP at SLAC operated at s=29 GeV. The fractions of decays into one and three charged particles are 0.8690.0020.003 and 0.1300.0020.003, respectively. © 1985 The American Physical Society.